2000
DOI: 10.1029/1999je001119
|View full text |Cite
|
Sign up to set email alerts
|

The state, potential distribution, and biological implications of methane in the Martian crust

Abstract: Abstract. The search for life on Mars has recently focused on its potential survival in deep (>2 km) subpermafrost aquifers where anaerobic bacteria, similar to those found in deep subsurface ecosystems on Earth, may have survived in an environment that has remained stable for billions of years. An anticipated by-product of this biological activity is methane. The detection of large deposits of methane gas and hydrate in the Martian cryosphere, or as emissions from deep fracture zones, would provide persuasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…The conditions on icy Solar System bodies such as Enceladus, Europa, Mars and comets have long been considered as potential for clathrate formation (Max & Clifford 2000;Prieto-Ballesteros et al 2005;Marboeuf et al 2010;Bouquet et al 2015). Clathrates are leading candidates for the storage of gases such as CH 4 and CO 2 in the Solar System (Prieto-Ballesteros et al 2005;Mousis et al 2015b;Bouquet et al 2015); therefore understanding the kinetics and thermodynamics of clathrate hydrates under planetary conditions is important.…”
Section: Introductionmentioning
confidence: 99%
“…The conditions on icy Solar System bodies such as Enceladus, Europa, Mars and comets have long been considered as potential for clathrate formation (Max & Clifford 2000;Prieto-Ballesteros et al 2005;Marboeuf et al 2010;Bouquet et al 2015). Clathrates are leading candidates for the storage of gases such as CH 4 and CO 2 in the Solar System (Prieto-Ballesteros et al 2005;Mousis et al 2015b;Bouquet et al 2015); therefore understanding the kinetics and thermodynamics of clathrate hydrates under planetary conditions is important.…”
Section: Introductionmentioning
confidence: 99%
“…Such life might well resemble the anaerobic bacterial communities found in the deep biosphere of the Earth (Stevens and McKinley, 1995). This possibility has been highlighted by the recent proposed detection of methane in the martian atmosphere (Formisano et al, 2004;Krasnopolsky et al, 2004;Muma et al, 2004)•a constituent that may be derived from abiotic processes, such as volcanism and the serpentization of basalt, or potentially be emitted from subsurface methanogenic microorganisms (Farmer, 1996;Fisk and Giovannoni, 1999;Wallendahl and Treiman, 1999;Max and Clifford, 2000;Krasnopolsky et al, 2004). Whether life did, in fact, originate and persist is of course one of the central questions of martian science.…”
Section: Resultsmentioning
confidence: 98%
“…Such environments comprise a vast habitable zone that may support more than half of the Earth's total biomass (Gold, 1992). Of particular relevance for Mars are chemolithoautotrophic forms of life that utilize hydrogen, methane, and sulfur (Boston et al, 1992;Max and Clifford, 2000). On Earth, such strategies have been observed over a broad range of envi-ronmental extremes of temperature, pH, and salinity (e.g., Rothschild and Mancinelli, 2001).…”
Section: C2 Were Habitable Environments Present On Earlymentioning
confidence: 99%
“…At the top of the hydrate stability zone (HSZ) CH 4 hydrate is in equilibrium with free CH 4 gas and water ice. The base of the HSZ, where CH 4 hydrate dissociates to form dissolved CH 4 and liquid water, is expected to lie at approximately 6 km depth below the surface in pure water systems [Max and Clifford, 2000]. Likewise, CO 2 hydrates are predicted to be stable to depths of approximately 5 km in pure water systems [Hoffman, 2000].…”
Section: Gas Hydrate Stability In High Salinity Brinesmentioning
confidence: 99%
“…[4] Both CH 4 and CO 2 hydrate are predicted to be stable within the Martian subsurface if the guest molecule gas is present in requisite concentrations [Longhi, 2006;Miller and Smythe, 1970;Max and Clifford, 2000]. Several studies have suggested gas hydrate dissociation as a mechanism for forming surface erosional features [Hoffman, 2000;Max and Clifford, 2001], and as significant subsurface or polar reservoirs of ancient water, CO 2 , and CH 4 which may have contributed to a thicker greenhouse atmosphere early in Martian history [Jakosky et al, 1995;Miller and Smythe, 1970;Prieto-Ballesteros et al, 2006].…”
Section: Introductionmentioning
confidence: 99%